The use of TikTok application and its effect on students' learning behavior - Efendy, Rustan; Nur, Haerani; Jaya, Muh. Ilham; Ihram, Nurul Al (Jurnal Inovasi Teknologi Pendidikan, 2024)
This study took samples at public high schools (SMAN) Barru district, South Sulawesi which aims to examine the level of use of the TikTok application on student learning behavior and at the same time analyze whether the use of the TikTok application has a significant effect on student learning behavior at SMAN Barru Regency. The research approach used is quantitative with a correlation type of research. The population in this study amounted to 108 students with a sample of 52 students selected using the Slovin technique. The data collection technique used a questionnaire. The data collected were then analyzed using descriptive statistical analysis techniques and inferential statistical analysis. The results of this study are (1) the results of the One Sample T-test test on the use of the TikTok application (X) obtained a value of 68.4% in the high category. (2) The results of the One Sample T-test test on learning behavior (Y) obtained a value of 70.3% in the good category. (3) the results of the Pearson product-moment correlation test obtained 0.410 indicate that there is a strong enough relationship. It is known that r count 0.410> r table 0.273, the Pearson correlation in this study is positive and the significance value is 0.00 <0.05, so there is a significant relationship (4) the results of the simple linear regression test show that the regression coefficient value is 0.395, so that every 1% increase in discounting, learning behavior increases by 0.395. The conclusion is that the use of the TikTok application has a significant effect on the learning behavior of students at SMAN Barru Regency, but based on the results of the coefficient of determination test obtained by R square 0.168, it was found that the level of influence was still low, namely 16.8%.